From prenatal diagnosis to postnatal stability: a case of isolated type II congenital pulmonary airway malformation - Dadmal, Swapnil; Kamble, Shubham; P. V., Shilpa; Jategaonkar, Smita; Jain, Manish (International Journal of Contemporary Pediatrics, 2025)
Congenital pulmonary airway malformation (CPAM) is the most common congenital lung anomaly. CPAM is characterized by multiple cysts of varying diameter, of embryological origin. With advances in prenatal imaging, it is frequently detected antenatally. We report a male neonate with antenatal diagnosis of CPAM in the lungs at 22 weeks of gestation. The baby was delivered at 39 weeks via planned cesarean section, weighing 2425 gm, and had mild transient tachypnea after birth. Postnatal imaging confirmed multiple thin-walled cysts in the right lung, without compression of adjacent structures. No associated anomalies were found. The neonate was managed conservatively and discharged with multidisciplinary follow-up. This case highlights the possibility of a benign course in asymptomatic CPAM type II, underscores the role of prenatal and postnatal imaging, and discusses current controversies regarding conservative versus surgical management.